Simultaneous Enhancement of Electrical and Optical Properties of Transparent Conducting RuO2 Nanosheet films by Facile Ultraviolet-Ozone Irradiation - Jong Wook Roh; Weon Ho Shin; Hyun-Sik Kim; Se Yun Kim; Sang-il Kim (Applied Sciences, 2020)
The enhancement of electrical and optical properties in transparent conducting electrodes has attracted significant interest for their application in flexible electronic devices. Herein, a method for the fabrication of transparent conducting films is proposed. In this approach, RuO2 nanosheets are synthesized by a simple chemical exfoliation method and deposited as conducting films by repeated Langmuir–Blodgett coating. For enhancing the electrical and optical properties of the films, ultraviolet-ozone irradiation is applied between the repeated coatings for the removal of residual organic materials from the chemically exfoliated nanosheets. We observe that by applying ultraviolet-ozone irradiation for 30 min, the sheet resistance of the films decreases by 10% and the optical transmittance is simultaneously enhanced. Facile ultraviolet-ozone irradiation is shown to be an effective and industrially friendly method for enhancing the electrical and optical properties of oxide nanosheets for their application as transparent conduction electrodes.